Effect of rotary instrumentation and of the association of calcium hydroxide and chlorhexidine on the antisepsis of the root canal system in dogs - Soares, Janir Alves; Leonardo, Mario Roberto [UNESP]; da Silva, Léa Assed Bezerra [UNESP]; Tanomaru Filho, Mario [UNESP]; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2006)
This study aimed at evaluating the antisepsis of the root canal system (RCS) and periapical region (PR) provided by rotary instrumentation associated with chlorhexidine + calcium hydroxide as intracanal medicament. Chronic periapical lesions were induced in 26 pre-molar roots in two dogs. After microbiological sampling, automatic instrumentation using the Profile system and irrigation with 5.25% sodium hypochlorite solution, with a final rinse of 14.3% EDTA followed by profuse irrigation with physiological saline were carried out in 18 root canals. After drying the canals, a paste based on calcium hydroxide associated with a 2% chlorhexidine digluconate solution was placed inside them. After 21 days, the medication was removed, leaving the root canals empty and coronally sealed. After 96 hours, a final microbiological sample was obtained, followed by histomicrobiological processing by the Brown & Brenn method. Eight untreated root canals represented the control group (C-G). Based on the Mann-Whitney test at a confidence level of 5% (p < 0.05), the procedures of antisepsis used offered significant efficacy (p < 0.05) resulting in 100.0% of the canals free of microorganisms. In the C-G, an elevated incidence of various microbial morphotypes was confirmed in all sites of the RCS, with the presence of microbial colonies in the periapical region. In contrast, the experimental group showed a similar pattern of infection in the RCS, although less intense and a reduced level of periapical infection (p < 0.05). It was concluded that adequate instrumentation followed by the application of calcium hydroxide + chlorhexidine offered significant elimination of microorganisms.
Keywords: Calcium hydroxide; Chlorhexidine; Endodontics; Microbiology; bone cement; calcium hydroxide; chlorhexidine; topical antiinfective agent; animal; animal model; dog; drug combination; endodontics; instrumentation; microbiology; tooth pulp; Animals; Anti-Infective Agents, Local; Bone Cements; Calcium Hydroxide; Dental Pulp Cavity; Dogs; Drug Combinations; Models, Animal; Root Canal Preparation